2015
DOI: 10.1016/j.jmbbm.2015.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Microarchitectural and mechanical characterization of the sickle bone

Abstract: Individuals with sickle cell disease often experience acute and chronic bone pain due to occlusive events within the tissue vasculature that result in ischemia, necrosis, and organ degeneration. Macroscopically, sickle bone is identified in clinical radiographs by its reduced mineral density, widening of the marrow cavity, and thinning of the cortical bone due to the elevated erythroid hyperplasia accompanying the disease. However, the microstructural architecture of sickle bone and its role in mechanical func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…These studies revealed that thalassemia mice exhibit the same weak bone phenotype as the thalassemia patients [93,94,95]. Similarly, sickle cell disease mice are characterized by low BMD and harmful alterations in the microarchitecture and mechanics of bones [96,97].…”
Section: Bone Homeostasis In Iron Overloadmentioning
confidence: 99%
“…These studies revealed that thalassemia mice exhibit the same weak bone phenotype as the thalassemia patients [93,94,95]. Similarly, sickle cell disease mice are characterized by low BMD and harmful alterations in the microarchitecture and mechanics of bones [96,97].…”
Section: Bone Homeostasis In Iron Overloadmentioning
confidence: 99%
“…Additionally, bone complications-associated joint pain is common in SCD with about 50% adults developing avascular osteonecrosis due to loss of blood supply to the femoral head in addition to osteoporosis and osteopenia ( 12 14 ). Femurs from transgenic sickle mice exhibit altered microstructure with 40% reduced mechanical strength compared to control mice ( 15 ). In addition to sudden and intractable acute pain, chronic joint and back pain in combination with reduced bone strength could contribute to difficulty in mobility and subsequent postural adjustment to compensate for the pain, i.e., change in gait ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…29 Because of the increased intramedullary hematopoiesis leading to cortical expansion and thinning of skull bones in SCD, these bones may be particularly vulnerable to bleeding associated with infarctions. 30 Evidence of bone infarction can be seen on MRI, but the number of infarctions may be underestimated because not all patients in this report had an MRI. Nonetheless, 15 patients (60.0%), including four of the five patients who presented with periorbital edema, had clear evidence of skull bone infarction.…”
Section: Discussionmentioning
confidence: 69%
“…Outside of infancy, sickling occurs most commonly in the long bones of the humerus, followed by the tibia, and then the femur, but it can also occur less commonly in skull bones . Because of the increased intramedullary hematopoiesis leading to cortical expansion and thinning of skull bones in SCD, these bones may be particularly vulnerable to bleeding associated with infarctions . Evidence of bone infarction can be seen on MRI, but the number of infarctions may be underestimated because not all patients in this report had an MRI.…”
Section: Discussionmentioning
confidence: 83%